EVT‐701 is a novel selective and safe mitochondrial complex 1 inhibitor with potent anti‐tumor activity in models of solid cancers - Raquel Luna Yolba; Virgile Visentin; Caroline Hervé; Johanna Chiche; Jean‐Ehrland Ricci; Jérôme Méneyrol; Michaël R. Paillasse; Nathalie Alet (Pharmacology Research & Perspectives, 2021)
Abstract Targeting the first protein complex of the mitochondrial electron transport chain (MC1) in cancer has become an attractive therapeutic approach in the recent years, given the metabolic vulnerabilities of cancer cells. The anticancer effect exerted by the pleiotropic drug metformin and the associated reduction in hypoxia‐inducible factor 1α (HIF‐1α) levels putatively mediated by MC1 inhibition led to the development of HIF‐1α inhibitors, such as BAY87‐2243, with a more specific MC1 targeting. However, the development of BAY87‐2243 was stopped early in phase 1 due to dose‐independent emesis and thus there is still no clinical proof of concept for the approach. Given the importance of mitochondrial metabolism during cancer progression, there is still a strong therapeutic need to develop specific and safe MC1 inhibitors. We recently reported the synthesis of compounds with a novel chemotype and potent action on HIF‐1α degradation and MC1 inhibition. We describe here the selectivity, safety profile and anti‐cancer activity in solid tumors of lead compound EVT‐701. In addition, using murine models of lung cancer and of Non‐Hodgkin's B cell lymphoma we demonstrated that EVT‐701 reduced tumor growth and lymph node invasion when used as a single agent therapy. LKB1 deficiency in lung cancer was identified as a potential indicator of accrued sensitivity to EVT‐701, allowing stratification and selection of patients in clinical trials. Altogether these results support further evaluation of EVT‐701 alone or in combination in preclinical models and eventually in patients.